New symmetric azobenzene molecules of varied central cores: Synthesis and characterisation for liquid crystalline properties. Issue 9 (15th July 2017) - Srinivasa, H. T.
ABSTRACT: A new series of azobenezene liquid crystals (LCs) was designed and synthesised by known and straightforward methods. The central connecting cores of the molecules varied viz., benzene/naphthalene/biphenyl. The molecular structures were confirmed by infrared, UV, nuclear magnetic resonance spectroscopic techniques. The LC texture and thermal phase behaviours were investigated by polarising optical microscopy and differential scanning calorimetry. Smectic B phase was found in biphenyl-derived azobenzene ester. The effect of central core on LC properties was investigated. The decreased angle at central connecting core suppressed the melting points, phase transition temperatures without losing LC properties, whereas, in moderate angle compounds LC properties were suppressed. The compounds with increased angle at central core favours rich mesomorphism. Graphical Abstract: